Refleksi Dalam Pembelajaran Sejarah Berwawasan Kebangsaan Dari Peristiwa Sejarah Sepak Bola Indonesia Pada AFF 2010 - Wibowo, Satrio; Agung, Dewa Agung Gede; Hudiyanto, R. Reza (Jayapangus Press, 2025)
The focus of this article's discussion is on national-oriented history learning based on the 2010 AFF football history events. The aim of this research is to examine the historical events of Indonesian Football at the 2010 AFF as a reflection in national-oriented history learning. The method used in this research is the historical research method which consists of four stages, including heuristics, source criticism, interpretation, and historiography. The sources used in this research are primary sources which include newspaper archives and video replays of the 2010 AFF matches. Apart from that, secondary sources are also used which consist of books, journals and previous research that are relevant to the themes and problems studied. . The results of this research are about how students respond to a historical event as a form of learning that must be examined critically and able to be reflected in real life. This study can be used as material for reflection to take better steps in the future. Like the AFF event in 2010, it can be used as a source of motivation for Indonesian football to be better, not the opposite. Because this is a point where initially success is not permanent but can experience change. One of the reasons is because there was an error at the end. If this is not addressed well, it will potentially cause disappointment. Of course, this phenomenon can be an important lesson, namely understanding that initial assessments do not always have a big and dynamic influence. By seeing or reflecting on this event, students are expected to be able to respond to national feelings wisely, one of which is through learning history with a national perspective.